The beneficial role of N-acetylcysteine as an adjunctive drug in treatment of COVID-19 patients in a tertiary care hospital in India: an observational study - Bhattacharya, Raja; Mondal, Maitry; Naiya, Subhendu Bikash; Lyngdoh, Lamsaka; Mukherjee, Rishav; Singh, Prabhat K. (International Journal of Research in Medical Sciences, 2020)
Background: N-acetyl cysteine, a mucolytic agent, demonstrates free radical scavenging and anti-inflammatory properties, and prevents endothelial dysfunction by inhibition of NF-KB and formation of no adducts. This has a potential role to tackle cytokine storms, endothelial dysfunction and prothrombotic state observed in COVID-19 manifestations like ARDS and Multi organ dysfunction. Methods: Institution based descriptive cross sectional study, 164 patients from laboratory confirmed RT PCR positive COVID-19 patients, in the study period from 27th May 2020 to 10th August 2020, were assessed, in medical college Kolkata, a dedicated COVID-19 care facility. Results: It was observed that moderate-severe patients who received N-acetyl cysteine along with standard therapy had average hospital stay duration of 12 days, higher rate of discharge, average duration of oxygen therapy of 8 days, less number of deaths and reduced transfer to critical care facilities. Conclusions: N-acetyl cysteine can be considered as an adjunctive therapy with standard protocol driven care, due to its beneficial anti-inflammatory and free radical scavenging properties.